2017
DOI: 10.1080/10749357.2017.1282413
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of mechanisms of gait speed change post-stroke. Part 2: exercise capacity, muscle activation, kinetics, and kinematics

Abstract: Background Regaining locomotor ability is a primary goal in stroke rehabilitation and is most commonly measured using changes in self-selected walking speed. However, walking speed cannot identify the mechanisms by which an individual recovers. Laboratory-based mechanistic measures such as exercise capacity, muscle activation, force production, and movement analysis variables may better explain neurologic recovery. Objectives The objectives of this systematic review are to examine changes in mechanistic gait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 55 publications
1
51
0
1
Order By: Relevance
“…Step length and stride length are considered closely connected to gait speed [74]. However, even though a difference between groups was not detectable with regards to gait speed, our analyses showed that step length (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Step length and stride length are considered closely connected to gait speed [74]. However, even though a difference between groups was not detectable with regards to gait speed, our analyses showed that step length (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…As robust individuals are known to have better HRQoL than frail individuals, the results in the present study therefore likely overestimate EQ-5 L-5D scores and underestimate the decrease in HRQoL from 3 to 18 months. Of the Fried criteria applied in this study, weight loss, self-reported exhaustion, and low physical activity refer to the participants' pre-stroke states, while slow gait speed and low grip strength had to be assessed poststroke and may have been influenced by the stroke incident [55,56]. We have adjusted for stroke severity, but this may still comprise a methodical challenge in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Foot drop interferes with ankle dorsiflexion during the swing phase of gait and contributes to the disruption in weight acceptance and weight transfer in the initial foot contact and stance phases [ 7 ]. The most evident alterations in gait, besides a marked asymmetry, include walking speed reduction, longer durations of double-stance and paretic swing phases, reduced paretic single-stance phase duration, cadence, and stride length [ 3 , 8 ], asymmetric postural behavior during walking and standing [ 9 ], altered kinematics, and reduced ankle push-off ability in terminal stance [ 10 , 11 ]. In this context, gait impairments cause difficulties with performing the activities of daily living and mobility, thus reducing independence and quality of life [ 12 ].…”
Section: Introductionmentioning
confidence: 99%